BEHAVIOUR OF PLASMA HYDROGENATED n-TYPE SILICON IN AQUEOUS FLUORIDE MEDIA (Sciences & Technology. A, exactes sciences, 2003)
In this paper we have investigated the electrochemical behaviour, in the dark, of hydrogenated n-type silicon (n-Si (H)) as function of the plasma hydrogenation duration. We also study the pore size microstructures and the flat band potential Vfb. The results are compared with non-hydrogenated n-Si. To              explain this                results     we           had proposed electro- chemical reactionary mechanism, in which one of the species created by the plasma accelerates the oxidation of the silicon even at anodic polarisation.This reaction is SiH2 + 2F-att ==> SiF2 + 2e- + H2 through it two electrons are injected in the conduction band. Then we had concluded that the mass loss and porous material formation is seriously affected by the hydrogenation.